Characteristics of Candied Dried Orange Peel by Soaking Guava Leaf Extract (Psidium Guajava. L) - Welly Deglas; Fransiska Fransiska; Tjhang Winny Kurniawan; M. Anastasia Martiyanti (Program Studi Teknologi Pangan, 2023)
This study aims to explain and describe the sensory characteristics of dried candied orange peel soaked in guava leaf extract, as well as to perform organoleptic tests on dried candied orange peel. The completely randomized design (CRD) method was used with 4 treatments involving soaking guava leaf extract for 1 hour, 2 hours, 3 hours and 4 hours, with 4 replications. The results showed that the longer the soaking process, the water content in dried sweets increased, because the ingredients absorbed more water. The water content of dried candied orange peel in all treatments ranged from 15.15% to 24.19%, meeting the quality standard of SNI (1988) which requires a maximum moisture content of 25%. Organoleptic testing showed significant differences in terms of taste, texture, and preferences between samples, which can be seen from the calculated F value which is greater than the F table of 5% and F table of 1%. However, there was no significant difference in the aroma organoleptic test. Overall, the panelists tended to like dried candied orange peel soaked for 3 hours (355) with a score of 6.20, indicating a high level of preference.